Supervised moderate intensity resistance exercise training improves strength in Special Olympic athletes - Tamse, T. R.; Tillman, M. D.; Stopka, C. B.; Weimer, A.; Abrams, G. L.; Issa, I. M. (The Journal of Strength and Conditioning Research, 2010)
The purpose of this study was to examine the effects of a moderate intensity resistance training program on Special Olympic athletes (SOAs) and similarly aged typically developed volunteers (TDs) who also served as coaches. Fifteen SOAs and 17 TDs participated (age range 19-24 years). The intervention consisted of resistance training: 1 set, 8-12 reps, over 10-12 sessions, on Med-X weight equipment. Exercises tested were seated row (SR), leg curl (LC), leg extension (LE), chest press (CP), and the abdominal crunch (AC). The weight lifted, and the amount of repetitions performed at the beginning and end of training, were used to determine the predicted 1 repetition max (1RM). A 2-way (2:group × 2:time) analysis of variance was computed for each exercise. Time main effects were detected, which indicated that predicted 1RM increased significantly for all participants. Specifically, these were the SR (F(1,30) = 99.238, p < 0.001); the LC (F(1,30) = 91.578, p < 0.001); the LE (F(1,30) = 83.253, p < 0.001); the CP (F(1,30) = 53.675, p < 0.001); and the AC (F(1,30) = 57.759, p < 0.001). The predicted 1RM values increased between 25 and 50% across the exercises tested. There were no group main effects or interactions. Thus, with minimal training time, both similar and significant strength gains can be accomplished by both SOAs and TDs, respectively. Supervised moderate intensity resistance training is recommended for the populations tested and may result in vocational and athletic performance gains.